2014
DOI: 10.1186/1476-069x-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Association of placenta organotin concentrations with growth and ponderal index in 110 newborn boys from Finland during the first 18 months of life: a cohort study

Abstract: BackgroundHumans are exposed to tributyltin (TBT), previously used as an antifouling paint in ships, mainly through fish consumption. As TBT is a known obesogen, we studied the association of placenta TBT and other organotin compounds (OTCs) with ponderal index (PI) and growth during the first 18 months of life in boys.MethodsIn a prospective Finnish study, 110 placenta samples were collected from mothers of boys born in 1997–1999 with (n = 55) and without (n = 55) cryptorchidism. To account for the original s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 52 publications
0
37
0
2
Order By: Relevance
“…Organotins have also been found in appreciable levels in house dust, suggesting that much of the population is exposed on a regular basis [48]. A recent study showed a positive correlation between placental TBT levels and weight gain in male infants at 3 months of age [22]. Therefore, TBT exposure is associated with weight gain both in animals and in humans and future human biomonitoring studies are justified and relevant to the obesity epidemic.…”
Section: Transgenerational Effects Of Edcs and Obesogensmentioning
confidence: 99%
“…Organotins have also been found in appreciable levels in house dust, suggesting that much of the population is exposed on a regular basis [48]. A recent study showed a positive correlation between placental TBT levels and weight gain in male infants at 3 months of age [22]. Therefore, TBT exposure is associated with weight gain both in animals and in humans and future human biomonitoring studies are justified and relevant to the obesity epidemic.…”
Section: Transgenerational Effects Of Edcs and Obesogensmentioning
confidence: 99%
“…Using the average seafood consumption data of 0.067 kg/day provided by Lee et al [21], the dose of TBT used in the present study is below those doses to which people may be exposed. Recently, a human epidemiological study showed that placenta TBT is associated with increased weight gain during the first three months of life [22], which indicated a role for TBT pollution in the development of obesity. In the present study, 0.5 μg/kg TBT treatment already produced a prominent obesity-related effect.…”
Section: Discussionmentioning
confidence: 99%
“…De plus, le dosage des perturbateurs endocriniens est réalisé dans les urines, ou le sang du cordon, sur un prélèvement unique, alors que la répétition des mesures sur plusieurs prélèvements serait indispensable pour une bonne appréciation de l'exposition [27], en particulier pour les polluants à demi-vie courte comme les phthalates et les bisphénols. Pour certains polluants persistants, le placenta constituerait un bon reflet de l'exposition in utero [28]. Pour SYNTHÈSE REVUES autant, en considérant toutes ces limites, les différentes études s'accordent à reconnaître la plausibilité de l'hypothèse d'un impact des perturbateurs endocriniens dans l'étiologie de l'épidémie d'obé-sité et/ou des maladies métaboliques associées, en particulier pour les polluants persistants [4,29].…”
Section: Effets Métaboliques Des Polluants Et éTudes éPidémiologiquesunclassified
“…Pour SYNTHÈSE REVUES autant, en considérant toutes ces limites, les différentes études s'accordent à reconnaître la plausibilité de l'hypothèse d'un impact des perturbateurs endocriniens dans l'étiologie de l'épidémie d'obé-sité et/ou des maladies métaboliques associées, en particulier pour les polluants persistants [4,29]. Par exemple, la concentration placentaire de TBT est associée positivement avec le poids des garçons pendant les trois premiers mois de la vie [28]. Le DDT, qui est un oestrogéno-mimétique, ou son métabolite, le DDE (dichlorodiphenyldichloroethylene) qui exerce une action antagoniste vis-à-vis des androgènes, auraient des actions obésogènes chez les garçons (et pas chez les filles) [30,31] après une exposition intra-utérine.…”
Section: Effets Métaboliques Des Polluants Et éTudes éPidémiologiquesunclassified